CHANGES IN THE INTESTINAL MICROFLORA IN THE BABY AND THE WAYS OF THEIR CORRECTION - Yodgorova N.T; Fayzullaeva Z.R; Mamatmusaeva F.Sh. (Scholar Express Journals, 2022)
To study the effect of probiotics on the intestinal microbiocenosis of young children who are naturally and artificially fed
Keywords: natural and artificial nutrition of young children; normal intestinal microflora; dysbacteriosis